Cohesion, Coherence, Cooperation : European Spatial Planning Coming of Age? - Faludi, Andreas (RTPI library series., 2010)
Since its foundation the European Union has gradually developed policies that are aimed at achieving increased economic and social cohesion. This book examines the most recent of these, the concept of territorial cohesion. Territorial cohesion is the pursuit of balanced development, competitiveness, sustainable development, and good governance. These concerns are most readily addressed by the formulation of spatial strategies under the umbrella of spatial planning, that brings together a multitude of public and private actors in a process that requires cohesion, coherence and co-operation. This book traces the development of spatial planning at European level and argues that spatial planning can become a vehicle, not only for territorial cohesion, but for EU policy generally.